2021
DOI: 10.1002/pat.5583
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new aliphatic poly(ester‐carbonate)s bearing amino groups based on photolabile protecting group and evaluation of antibacterial property

Abstract: Amino‐functionalized six‐membered cyclic carbonate 5‐((2‐nitrobenzyl) amino)‐1,3‐dioxan‐2‐one (NBAC) was synthesized with 2‐nitrobenzyl group as photolabile protecting group. The following copolymerization was carried out by using l‐lactide as comonomer and Sn (Oct)2 as catalyst. The amino‐functionalized polymer P(LA‐co‐AC) was obtained by ultraviolet irradiation of P(LA‐co‐NBAC) to remove the protecting group. The structures of products were confirmed by 1H nuclear magnetic resonance (NMR) and 13C NMR analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Chen et al [ 336 ] obtained a series of copolymers with a pendant amino group by ROP initiated with a tin compound during the copolymerization of L-lactide and specially synthesized cyclic carbonate ((2-nitrobenzyl) amino)-1,-3-dioxan-2-one (NBAC). The use of carbonate with a nitrobenzyl group allowed the troublesome process of deprotection of functional groups.…”
Section: Synthetic Biodegradable Polymers With Antibacterial Propertiesmentioning
confidence: 99%
“…Chen et al [ 336 ] obtained a series of copolymers with a pendant amino group by ROP initiated with a tin compound during the copolymerization of L-lactide and specially synthesized cyclic carbonate ((2-nitrobenzyl) amino)-1,-3-dioxan-2-one (NBAC). The use of carbonate with a nitrobenzyl group allowed the troublesome process of deprotection of functional groups.…”
Section: Synthetic Biodegradable Polymers With Antibacterial Propertiesmentioning
confidence: 99%
“…Further, we found that the introduction of bactericidal groups such as amino cations, can not only improve the hydrophilicity, but also directly endow the material with antibacterial properties. [34][35] In this study, we synthesized a macromolecule with pendant primary amine groups named poly (L-lactide-co-5-amino-1,3-dioxan-2-one) (P(LA-co-AC)), which mimicked antimicrobial peptides (AMP) 36 . Based on reports in the literature, this AMP structure could attach to the microbial membrane via electrostatic attractions between their cationic groups and the anionic membrane's surface.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 In this study, we synthesized a macromolecule with pendant primary amine groups, named poly (L-lactide-co-5-amino-1,3dioxan-2-one) (P(LA-co-AC)), which mimicked antimicrobial peptides (AMP). 36 Based on reports in the literature, this AMP structure could attach to the microbial membrane via electrostatic attractions between their cationic groups and the surface of the anionic membrane. When this occurs, hydrophobic chains intercalate into the microbial membrane to induce membrane destabilization and subsequent leakage of cytoplasmic content, leading to lysis.…”
Section: Introductionmentioning
confidence: 99%